The relationship between serum uric acid and metabolic syndrome in premenopausal and postmenopausal women in the Jinchang Cohort. (1st February 2017) - He, Shi-Jiao; Chan, Cynthia; Xie, Zhi-Dong; Shi, Dian; Hu, Xiao-Bin; Li, Hai-Yan; Wang, Dennis; Wang, Min-Zhen; Bai, Ya-Na
Abstract: The aim of the study was to explore the association between serum uric acid (SUA) and metabolic syndrome (MetS) in premenopausal and postmenopausal women in the Jinchang Cohort. We studied 3808 female Jinchuan Nonferrous Metals Corporation workers aged 40–60 years. Cohort data from epidemiological surveys and medical exams were used. MetS was defined using the 2009 Joint Interim Society criteria. The relationship between SUA and MetS was evaluated using multiple logistic regression after adjusting for potential confounders. MetS and hyperuricemia were more prevalent in postmenopausal women than premenopausal ones (35.3% versus 15.2% and 9.2% versus 4.2%, respectively). Premenopausal and postmenopausal women with hyperuricemia had 2.81 (95% CI: 1.72–4.61) and 2.10 (95% CI: 1.44–3.08), respectively, times the odds of having MetS than their counterparts without hyperuricemia. Even within normal SUA quartiles, only premenopausal women in the highest and second-highest quartile had 3.57 (95% CI: 2.24–5.68) and 2.78 (95% CI: 1.71–4.50), respectively, times the odds of having MetS than those in the lowest quartile. Even in the normal range, the odds ratios for MetS increased gradually according to SUA levels in all women (Ptrend < 0.001). In conclusion, there was a significant correlation between SUA levels and MetS, and the association was stronger in premenopausal women than postmenopausal ones.